Attitudes and motivation: the learning of Acrolect Malaysian English at a private college / Parilah M. Shah and Judy Ng Miang Koon - M. Shah, Parilah; Ng, Judy Miang Koon (2002)
This study investigated the reasons as to why the foreign students at Inti College Malaysia did not show good performance in the English language that is being used as the medium of instruction. It addressed the students' attitudes towards Acrolect Malaysian English and their motivation to learn the English language. A survey questionnaire was utilized to gather the data from students who were involved in the English Improvement Programme. Frequency analysis was performed on the data. The findings revealed that the students showed negative attitudes towards Acrolect Malaysian English. The preferred models were the native English speaker models, for instance Standard American English and Standard British English. In terms of motivation, the students were instrumentally motivated; more students indicated "strongly agree" and "agree" responses towards most of the items on this aspect than those on integrative motivation. In order to overcome the problem of students' negative attitudes, it is suggested that the administrators and lecturers emphasize the native speakers' variety in the classroom. Nevertheless, the Acroleet Malaysian English should also be made known to students through informal lessons such as during drama practices. This is important because the foreign students are exposed to the Aeroleet Malaysian English in their dealings with officers from the various administrative departments at Inti College.